LAND ALLOCATION STRATEGIES THROUGH GENETIC ALGORITHM APPROACHaA CASE STUDY (Global Journals of Research in Engineering, 2011)
Development of agriculture depends on optimal land allocation. The development towards optimal utilization of land under cultivation and thereby increasing the production of crops and profit with less fertilizer consumption have to be taken into consideration in agriculture planning. In this paper different agriculture strategies are developed and accordingly, single objective optimization models are formulated with net profit, production of crops and fertilizer consumption as objectives and availability of cultivable land, agriculture labor, agriculture machinery and water as constraints. To illustrate the models a case study of Visakhapatnam district, Andhra Pradesh, India is presented and are solved through GA.